The political culture of British communism, 1920-1991. - Communist Party of Great Britain; Communist Party of Great Britain. Archive Trust (East Ardsley, Wakefield, United Kingdom : Microform Academic Publishers, 2020)
National Congress was the supreme decision-making body of the Communist Party of Great Britain (CPGB). Congress delegates from across the Party's districts and branches met bi-annually in order to elect members to key political bodies, to vote on resolutions and on other policy issues, and to fraternise with fellow members and representatives of international communist parties. Congress was a hive of activity and often the scene of high political drama as tensions frayed and factions fought over the direction of the Party.
Date range: 1920-1991.
Keywords: Communist Party of Great Britain; Communist leadership -- Great Britain